HEORETICAL AND METHODOLOGICAL APPROACHES TO ASSESSING NATURAL AND GEOGRAPHICAL FACTORS IN TOURISM DEVELOPMENT - Odiljon Tobirov,; Xidoyatkhon Abdinazarova,; Azamjon Jobborov, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article examines theoretical and methodological approaches to assessing natural and geographical factors influencing tourism development. Based on a  synthesis  of  contemporary  scientific  literature,  the  study  analyzes  key  theoretical frameworks  that  explain  the  role  of  natural  conditions,  geographical  location,  and environmental resources in shaping tourism attractiveness and sustainability. Special attention is given to modern methodological tools, including Geographic Information Systems (GIS), multi-criteria decision analysis, and integrated qualitative–quantitative approaches used to evaluate tourism potential. The findings highlight that effective tourism  development  requires  a  holistic  assessment  framework  that  combines ecological, socio-economic, and spatial factors. The study emphasizes that adapting assessment  methodologies  to  regional  characteristics  enhances  strategic  planning, supports  sustainable  tourism  practices,  and  improves  policy  decision-making.  The article  contributes  to  tourism  geography  by  systematizing  existing  approaches  and outlining  methodological  directions  for  future  research  aimed  at  resilient  and environmentally responsible tourism development.